Increasing access to evidence-based treatment for child anxiety problems: online parent-led CBT for children identified via schools - Green, Iheoma; Reardon, Tessa; Button, Roberta; Williamson, Victoria; Halliday, Gemma; Hill, Claire; Larkin, Michael; Sniehotta, Falko F.; Ukoumunne, Obioha C.; Ford, Tamsin; Spence, Susan H.; Stallard, Paul; et al. (Child and adolescent mental health, 2023)
Background Anxiety problems are extremely common and have an early age of onset. We previously found, in a study in England, that fewer than 3% of children with an anxiety disorder identified in the community had accessed an evidence-based treatment (Cognitive Behavioural Therapy; CBT). Key ways to increase access to CBT for primary school-aged children with anxiety problems include (a) proactive identification through screening in schools, (b) supporting parents and (c) the provision of brief, accessible interventions (and capitalising on technology to do this). Method We provided a brief, therapist guided treatment called Online Support and Intervention (OSI) to parents/carers of children identified, through school-based screening, as likely to have anxiety problems. Fifty out of 131 children from 17 Year 4 classes in schools in England screened positive for ‘possible anxiety problems’ and 42 (84%) of these (and 7 who did not) took up the offer of OSI. We applied quantitative and qualitative approaches to assess children's outcomes and families' experiences of this approach. Results Inbuilt outcome monitoring indicated session on session improvements throughout the course of treatment, with substantial changes across measures by the final module (e.g. Child Outcome Rating Scale d = 0.84; Goal Based Outcomes d = 1.52). Parent engagement and satisfaction was high as indicated by quantitative and qualitative assessments, and intervention usage. Conclusions We provide promising preliminary evidence for the use of OSI as an early intervention for children identified as having anxiety problems through school-based screening.